A Tale of Two Taxes: Clean Energy Act 2011 (Cth) v Renewable Energy (Electricity) Act 2000 (Cth) - Fullarton, Alexander (Curtin University Business and Law, 2019)
Firstly, this paper defines a tax to establish a definition of a carbon tax and then examines the Clean Energy Act 2011 (Cth) (CE Act), which is considered to be a carbon tax. Secondly, it examines the Australian Renewable Energy (Electricity) Act 2000 (Cth) (REE Act) to ascertain if it functions as a tax on greenhouse gas emissions and is therefore also a carbon tax. It examines both pieces of legislation to compare and contrast them to establish the view that the REE Act is not a quota based system to limit greenhouse gas emissions (a ‘cap and trade’ system) but rather it is a carbon tax system. To do that the paper investigates various definitions of tax. It compares those definitions with the legislative intent and functions of the REE Act to answer the question – is the REE Act a carbon tax system? It concludes that the provisions of the REE Act function as a form of carbon tax. It also concludes that tax revenue, sourced from an excise on fossil fuel generated electricity, is specifically directed by government to a particular purpose – the revenue is hypothecated to support the burgeoning renewable energy industry in Australia. The REE Act taxing system functions by the creation of renewable energy certificates (RECs) by the operators of registered renewable energy generation installations. The RECs are intended to be surrendered as ‘tax tokens’ or coupons by the suppliers of fossil fuelled generated electricity. The RECs are subsequently traded on a market to any party registered to trade on a government supervised electronic market place – the Australian rec-registry. They can be, and often are, traded as a form of commodity speculation prior to surrender. However they are ultimately purchased by suppliers of fossil fuelled generated electricity to be surrendered to government agencies. Surrendering RECs is the only means by which the suppliers of fossil fuelled generated electricity can meet their commitments under the provisions of the REE Act. A fiscal penalty is applied for any shortfall or non-compliance in the number of RECs surrendered and no payment is made by government agencies for the surrendered RECs. A REC, purchased at a variable market value dependent on the economic forces of supply and demand, becomes a token or coupon for the payment of tax. The supply of RECs is dependent on the volume of electricity generated by registered renewable energy generation installations. The demand for RECs is created by the level of the renewable energy target as set annually by the Parliament of Australia. As operators of renewable energy generation installations are the only parties which can create RECs, and suppliers of fossil fuelled generated electricity are obliged to purchase RECs to meet their tax commitments the transfer of RECs subsidises Australia’s burgeoning renewable energy industry.